Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Harga Saham (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2017) - Apriyanto, Edwin B1031151060 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
ABSTRACTÂ Â Â Â Â The purpose of this study is to determine the effect of disclosure of Corporate Social Responsibility which consists of disclosure of Social-CSR, CSR-Environment, and Social-CSR with the share price of mining companies listed on the Indonesia Stock Exchange in 2016-2017. This research is an ex post facto research, the sample chosen using purposive sampling is as many as 70 annual reports of the company. This study uses data obtained by the documentation study method by obtaining data in the form of company annual reports. This study uses a method of data analysis in the form of descriptive analysis followed by a test of regression analysis requirements including normality test, heteroscedasticity test, autocorrelation test, and multicollinearity test. Hypothesis testing uses multiple regression analysis techniques.Â Â Â Â Â The results of the study show that (1) CSR-Economy has no significant effect on stock prices, (2) CSR-Environment has no significant effect on stock prices, (3) CSR-Social has a significant effect on stock prices, (4) CSR-Economy, CSR-environment, and CSR-Environment have no significant effect on stock prices simultaneously.Â Keywords: CSR-Economy, CSR-Environment, CSR-Social, Stock PricesRefferencesAgoes, Sukrisno dan I Cenik Ardana. (2009). Etika Bisnis dan Profesi Tantangan Membangun Manusia Seutuhnya. Jakarta: Salemba Empat.Dagiliene, Lina and Gokiene, Ruta. (2011). Valuation of Corporate Social Responsibility Reports. Journal of Economic and Management: 2011. 16.Djatmiko, H.â€Saatnya Menaburâ€. Majalah SWA 26 (XXI/19), 11 January 2006.Ervinah dan Mimin, W. (2012). â€œPengaruh Tingkat Pengungkapan Corporate Sosial Responsibility Terhadap Perubahan Harga Saham(Studi pada perusahaan pertambangan yang terdaftar di BEIâ€. Jurnal Akuntansii Riset, Prodi Akuntansi UPI. ISSN: 2086-2563.Fahmi, M. dan Herry P. (2017). Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Harga Saham Perusahaan Pertambangan Yang Terdaftar Di BEI. Vol 1, No 2, November 2017.Ghozali, I. 2013. Aplikasi Analisis Multivariate dengan Program IBM SPSS 21 Edisi , Semarang Badan Penerbit Universitas Diponegoro.GlobalÂ Â  Reporting Initiative, GRI Sustainability Reporting GuideLines G4. (Website http://www.globalreporting.org/, di akses 25 April 2017). Lako, Andreas (2011). Dekonstruksi CSR dan Reformasi Paradigma Bisnis & Akuntansi, Jakarta: Erlangga.Indriantoro, Nur, dan Bambang Supomo. (2016).Metode Penelitian Bisnis untuk Akuntansi dan Manajemen, Edisi Pertama, Jogjakarta: BPPE.Mia, Parves and Al-Mamun. (2011). Corporate Social Disclousure during the Global Financial Crisis. International journal of economics and Finance. Vol. 3, No. 6: November 2011.Mudji Utami dan Mudjilah Rahayu. (2003). â€œ Peranan Profitabilitas, Suku Bunga, Inflasi dan Nilai Tukar dalam Mempengaruhi Pasar Modal Indonesia Selama Krisis Ekonomiâ€. Jurnal Manajemen dan Kewirausahaan. (Vol. 5 No. 2). Hlm. 123-131.Nurdin, E., dan Cahyandito, M. F. (2006). Pengungkapan Tema-Tema Sosial dan Lingkungan dalam Laporan Tahunan Perusahaan terhadap Reaksi Investor. Jurnal KLH, (401), 1-17.Putri, Giovanni Aniza (2013). Pengaruh Pengungkapan CSR Terhadap Harga Saham Perusahaan Pertambangan yang Terdaftar di BEI Periode 2009-2001, (Jurnal Profita). Vol.18,No>1, ISSN 1411-0288. (http://journal.student.uny.ac.id/jurnal/artikel/552060/573).Samsinar, Anwar., Haerani, Siti., Pagalung, Gagaring. (2010). Pengaruh Pengungkapan Corporate Sosial Responsibility Terhadap Kinerja Keuangan Perusahaan dan Harga Saham. Makasar: Simposium Nasional Akuntansi 10Sayekti dan Wondobio. (2007). â€œPengaruh CSR Disclosure Terhadap Earning Response Coefficientâ€. Simposium Nasional Akuntansi.